The Plasmodium falciparum merozoite surface protein-1 19 KD antibody response in the Peruvian Amazon predominantly targets the non-allele specific, shared sites of this antigen - Sutton, Patrick L (BioMed Central, 2010)
BACKGROUND: Plasmodium falciparum re-emerged in Iquitos, Peru in 1994 and is now hypoendemic (< 0.5 infections/person/year). Purportedly non-immune individuals with discrete (non-overlapping) P. falciparum infections can be followed using this population dynamic. Previous work demonstrated a strong association between this population's antibody response to PfMSP1-19KD and protection against febrile illness and parasitaemia. Therefore, some selection for PfMSP1-19KD allelic diversity would be expected if the protection is to allele-specific sites of PfMSP1-19KD. Here, the potential for allele-specific polymorphisms in this population is investigated, and the allele-specificity of antibody responses to PfMSP1-19KD are determined. METHODS: The 42KD region in PfMSP1 was genotyped from 160 individual infections collected between 2003 and 2007. Additionally, the polymorphic block 2 region of Pfmsp1 (Pfmsp1-B2) was genotyped in 781 infection-months to provide a baseline for population-level diversity. To test whether PfMSP1-19KD genetic diversity had any impact on antibody responses, ELISAs testing IgG antibody response were performed on individuals using all four allele-types of PfMSP1-19KD. An antibody depletion ELISA was used to test the ability of antibodies to cross-react between allele-types. RESULTS: Despite increased diversity in Pfmsp1-B2, limited diversity within Pfmsp1-42KD was observed. All 160 infections genotyped were Mad20-like at the Pfmsp1-33KD locus. In the Pfmsp1-19KD locus, 159 (99.4%) were the Q-KSNG-F haplotype and 1 (0.6%) was the E-KSNG-L haplotype. Antibody responses in 105 individuals showed that Q-KNG and Q-TSR alleles generated the strongest immune responses, while Q-KNG and E-KNG responses were more concordant with each other than with those from Q-TSR and E-TSR, and vice versa. The immuno-depletion ELISAs showed all samples responded to the antigenic sites shared amongst all allelic forms of PfMSP1-19KD. CONCLUSIONS: A non-allele specific antibody response in PfMSP1-19KD may explain why other allelic forms have not been maintained or evolved in this population. This has important implications for the use of PfMSP1-19KD as a vaccine candidate. It is possible that Peruvians have increased antibody responses to the shared sites of PfMSP1-19KD, either due to exposure/parasite characteristics or due to a human-genetic predisposition. Alternatively, these allelic polymorphisms are not immune-specific even in other geographic regions, implying these polymorphisms may be less important in immune evasion that previous studies suggest.